O DISCURSO DA TELENOVELA SOBRE A HOMOSSEXUALIDADE - Trevizani, William Caldas (2002)
This research intended to show how the scientific knowledge about homosexuality has been very little approached in the soap-opera "Roda da Vida", displayed on Rede Record. It's a reference about how this subject has been treated on the television soap-operas. The theme has been shown on the television soap-operas as a way to create interest and identification on the audiences by treating real subjects.